Impactos da pandemia no direito à moradia e propostas para a proteção desse direito em tempos de crise: da urgência de se repensar a moradia para além de um objeto de consumo / Pandemic impacts on the right to housing and proposals for the protection of that right in times of crisis: from the urgency of the rethinking housing beyond and object of consumption - Santos, Paulo Junio Trindade dos; Marco, Cristhian Magnus de; Möller, Gabriela Samrsla (Revista de Direito da Cidade, 2021)
Resumo A cidade hoje é abordada desde uma perspectiva de objeto de consumo, cuja consequência é a privatização da moradia, a qual deixou de ser considerada um direito. O efeito é uma preocupação menor com políticas reguladoras dos mercados e protetivas aos cidadãos. Essa construção da cidade encontra seus limites em um cenário de pandemia, que transformou o modo de socializar, trabalhar e habitar: ter uma moradia significa, mais do que nunca, viver ou morrer. Na América Latina a pandemia poderá significar um acréscimo de 16 milhões pessoas em situação de extrema pobreza, o que implica pensar propostas para proteger os milhares que sentem os efeitos no direito à moradia, que vai desde a impossibilidade de pagar o aluguel como o de pagar por serviços básicos, o que atingirá com maior força pessoas que já sofrem com a falta de moradia ou déficit habitacional. A pesquisa analisa como a pandemia tem impactado o direito à moradia no Brasil e ao redor do mundo, bem como as medidas que os países vêm tomando para a proteção desse direito frente àquelas indicadas pelas organizações não governamentais. O objetivo é abordar a cidade a partir de uma perspectiva crítica, desvelando as nuances do atual paradigma do direito à moradia. Para a realização do trabalho utilizou-se bibliografias da linha teórica urbanística crítica e notícias que versam sobre o direito à moradia em um contexto de pandemia. Palavras-chave: Direito à moradia. Pandemia. Capitalismo estético. Financeirização da moradia. Urbanismo crítico. Abstract The city today is approached from a consumer object perspective, the consequence of which is the privatization of housing, which is no longer considered a right. The effect is less of a concern with policies that regulate markets and protect citizens. This construction of the city finds its limits in a pandemic (and post-pandemic) scenario, which implies thinking about proposals to protect the thousands who feel the effects on the right to housing, ranging from the impossibility of paying rent as paying for basic services, which will affect more strongly people who already suffer from homelessness or housing deficit. The research analyzes how the pandemic has impacted the right to housing in Brazil and around the world, as well as the measures that countries have been taking to protect this right in relation to those indicated by non-governmental organizations. The objective is to understand the impacts of the pandemic on the right to housing, going through phenomena around the world that imply a violation of this right and analyzing the proposals for the protection of the right, in order to verify whether they are protective for those most affected. The main results obtained show that the measures taken by the countries were temporary prohibitions on evictions, which have already expired, even with the continuation of the pandemic, and a bet on indirect aid to the detriment of direct aid in helping the most affected, as well as demonstrating that evictions and violations of the right to housing have not stopped or been reduced in a pandemic context. Keywords: Right to housing. Pandemic. Aesthetic capitalism. Financialization of housing. Critical urbanism.